Vertical Decentralisation and Urban Service Delivery in South Africa: Does Politics Matter?. (July 2014) - Cameron, Robert
<x xml:space="preserve">Abstract</x> Focusing on the case of South Africa, this study examines how decentralisation policies and inter‐party politics have affected urban service‐delivery responsibilities and resources. Service delivery does not appear to be worse off in Cape Town than in Johannesburg, even though the former is controlled by the opposition Democratic Alliance. While there have been political attempts to undermine the authority of its officials, the fiscal elements are protected by a relatively strong and well‐managed department of finance. Consequently, both donors and the national government steer money towards Cape Town because they know it can deliver on its obligations.